METHODOLOGIES OF TEACHING PHYSICAL EDUCATION FOR HEALTH (Fiep Bulletin - online, 2014)
The objective of this research was to make a rescue of information contained in teaching proposals of Physical Education associated with epidemic matters. The methodology used for this study was the bibliographical review. As result, it was found several information regarding healthy habits themes in school. These subjects should be given in a way that there would be an assimilation of these contents for adult life and not just at the school period. Physical Education must be consider as a way to develop healthy corporal culture, throughout the professional of this area, who is an agent that promotes health  education.
Keywords: Teaching proposal; Health education; Physical Education classes